Continuous flow electrophoretic separation — Recent developments and applications to biological sample analysis. Issue 1 (7th November 2019) - Stastna, Miroslava
Abstract: Continuous flow electrophoretic separation with continuous sample loading provides the advantage of processing volumes of any sizes, as well as the benefit of a real‐time monitoring and optimization of the separation process. In addition, the spatial separation of the sample enables collecting multiple separated components simultaneously and in a continuous manner. The separation is usually performed in mild buffers without organic solvents and detergents (sample biological activity is retained) and it is carried out without usage of a solid support in the separation space preventing the interaction of the sample with it (high sample recovery). The method is used for the separation of proteins/peptides in proteomic applications, and its great applicability is to the separation of the cells, cellular organelles, vesicles, membrane fragments, and DNA. This review focuses on the electrophoretic separation performed in a continuous flow and it describes various electrophoretic modes and instrumental setups. Recent developments in methodology and instrumentation, the integration with other techniques, and the application to the biological sample analysis are discussed as well.